2022
DOI: 10.3390/antibiotics11101436
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Transcriptomic Profiling Reveals the Inhibitory Effect of Hydroquinine on Virulence Factors in Pseudomonas aeruginosa

Abstract: Hydroquinine is an organic alkaloid compound that exhibits antimicrobial activity against several bacterial strains including strains of both drug-sensitive and multidrug-resistant P. aeruginosa. Despite this, the effects of hydroquinine on virulence factors in P. aeruginosa have not yet been characterized. We therefore aimed to uncover the mechanism of P. aeruginosa hydroquinine-sensitivity using high-throughput transcriptomic analysis. We further confirmed whether hydroquinine inhibits specific virulence fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…In general, L-arginine in P. aeruginosa is an essential molecule in the regulation of biofilm formation [ 39 ]. This supports the previous findings by Rattanachak et al [ 17 ] that hydroquinine could suppress QS-related gene expression, reduce virulence factor production, and impair biofilm formation in P. aeruginosa [ 17 ]. For another possible reason, hydroquinine may affect the production of carbamoyl phosphate, which is required for pyrimidine production [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In general, L-arginine in P. aeruginosa is an essential molecule in the regulation of biofilm formation [ 39 ]. This supports the previous findings by Rattanachak et al [ 17 ] that hydroquinine could suppress QS-related gene expression, reduce virulence factor production, and impair biofilm formation in P. aeruginosa [ 17 ]. For another possible reason, hydroquinine may affect the production of carbamoyl phosphate, which is required for pyrimidine production [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to the work of Rattanachak et al (2022), there were several changes in the transcriptomes of P. aeruginosa ATCC 27853 when treated with a hydroquinine concentration of 1.25 mg/mL for 1 h. This study revealed 157 upregulated genes and 97 downregulated genes in response to the treatment [ 17 ]. Several differentially regulated genes have already been investigated relating to virulence factors, such as quorum sensing and flagella assembly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations